2023
DOI: 10.3390/ijms24054493
|View full text |Cite
|
Sign up to set email alerts
|

POSS and SSQ Materials in Dental Applications: Recent Advances and Future Outlooks

Abstract: Recently, silsesquioxanes (SSQ) and polyhedral oligomeric silsesquioxanes (POSS) have gained much interest in the area of biomaterials, mainly due to their intrinsic properties such as biocompatibility, complete non-toxicity, the ability to self-assemble and to form a porous structure, facilitating cell proliferation, creating a superhydrophobic surface, osteoinductivity, and ability to bind hydroxyapatite. All the above has resulted in new developments in medicine. However, the application of POSS-containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 134 publications
0
8
0
Order By: Relevance
“…Previous studies concerning the incorporation of POSS particles into dental adhesives indicated a good dispersion and interaction between both materials [ 4 , 6 ]. It was found that while multifunctional MA-POSS concentrations that exceeded 10 wt.% led to a deterioration of mechanical properties, lower concentrations either did not adversely affect mechanical qualities or were even able to enhance them [ 6 , 10 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies concerning the incorporation of POSS particles into dental adhesives indicated a good dispersion and interaction between both materials [ 4 , 6 ]. It was found that while multifunctional MA-POSS concentrations that exceeded 10 wt.% led to a deterioration of mechanical properties, lower concentrations either did not adversely affect mechanical qualities or were even able to enhance them [ 6 , 10 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these materials still consist of aromatic MDI 107 . Recent studies have shown that POSS is effective as an osteoinductive modifier, allowing the biomaterials to bind and facilitate bone formation 107–118 . POSS was found to enhance osteoblast adhesion, osteocalcin production by cellular biomineralization, and alkaline phosphatase activity 115,119 .…”
Section: Introductionmentioning
confidence: 99%
“…107 Recent studies have shown that POSS is effective as an osteoinductive modifier, allowing the biomaterials to bind and facilitate bone formation. [107][108][109][110][111][112][113][114][115][116][117][118] POSS was found to enhance osteoblast adhesion, osteocalcin production by cellular biomineralization, and alkaline phosphatase activity. 115,119 The silicon in the core of POSS is believed to bind calcium ions and trigger the deposition of hydroxyapatite (HAp).…”
mentioning
confidence: 99%
“…Polyhedral oligomeric silsesquioxanes (POSS, SQ) with nanosized stable three-dimensional architectures have attracted increasing interest in the design of novel functional hybrid materials for applications in many important areas. [1][2][3][4][5] Recently, much attention has been paid to their use biomedical fields, [6][7][8][9][10] mainly due to their biocompatibility, non-toxicity, thermal and chemical stability, the ability to self-assembly and to form porous structures. [11,12] On top of that, they have been shown to facilitate cell proliferation and create superhydrophobic surfaces.…”
Section: Introductionmentioning
confidence: 99%